A sector-wide economic and environmental analysis on bioenergy production and emission consequences. Issue 4 (July 2019) - Kung, Shan-Shan; Zhang, Liguo; Gong, Xiaoyu; Kung, Chih-Chun
Mining and using depletable fossil fuel usually result in severe environmental problem such as climate change in the global scale and acid rain in the regional level. To improve sustainable development, it is important to substitute fossil fuel with renewable and clean energy sources. In this study we employ a partial equilibrium, price endogenous mathematical programming model to analyze how bioenergy development in Taiwan can (1) enhance domestic energy production, (2) reduce the carbon dioxide (CO2 ) and sulfur dioxide (SO2 ) emissions, and (3) protect the environment. The results show that the ethanol expands with an increase in gasoline price, but SO2 emission reduction would shrink because of a reduction in renewable electricity generation. Conversely, up to 10.4% of Taiwan's annual SO2 emission can be reduced in the face of higher coal and emission prices. A tradeoff between CO2 and SO2 emission reductions is perceived during the switch of production of liquid and nonliquid bioenergy. Policy implications such as technology selection, market operation, and government subsidy are also discussed.